Peran Digital Health untuk Manajemen Penanganan Pandemi COVID-19 di Indonesia: Systematic Literature Review - Rika Andriani; Fahmi Hakam (Lembaga Penerbitan Universitas Esa Unggul, 2022)
AbstractThe use of digital health increased in the COVID-19 pandemic. Various digital health technologies were used to help control the pandemic in this world. The main objective of this review is to explore the role of digital health technologies in managing and controlling the COVID-19 pandemic in Indonesia. A systematic literature review was conducted on three databases: Google Scholar, Google, and Garuda. This review found that digital health technologies were used in the main and supporting role in managing the COVID-19 pandemic. The main roles were contact tracing, surveillance, case management, laboratory data management, and early detection. The supporting roles were patient data management, knowledge related to COVID-19, teleconsultation, electronic medical records, and population mobility monitoring. It is recommended to have developed standards for digital health technologies and strengthen the collaboration among application developers.Keywords: COVID-19, digital health, eHealth, mHealth, health technology AbstrakPenggunaan digital health meningkat pada situasi pandemi COVID-19. Berbagai teknologi digital health digunakan untuk membantu manajemen penanganan pandemi di berbagai negara. Artikel ini bertujuan mengeksplorasi peran digital health dalam manajemen penanganan pandemi COVID-19 di Indonesia. Systematic literature review dilakukan pada tiga database, yaitu Google Scholar, Google, dan Garuda. Hasil review menemukan teknologi digital health yang digunakan di Indonesia memiliki dua jenis peran yaitu peran utama dan peran pendukung. Peran utama meliputi pelacakan kontak, surveilans, manajemen kasus, manajemen data laboratorium, dan deteksi dini. Peran pendukung meliputi manajemen data pasien, pemberian informasi COVID-19, telekonsultasi, rekam medis elektronik, dan pemantauan mobilitas penduduk. Untuk pengembangan aplikasi digital health direkomendasikan untuk memiliki standar pengembangan digital health dan memperkuat kerjasama antarpengembang aplikasi.Kata kunci: COVID-19, digital health, eHealth, mHealth, teknologi kesehatan